Studi Tentang Gambaran Infeksi Nosokomial di Bangsal Penyakit Dalam Lontara I Bawah Rumah Sakit Dr. Wahidin Sudirohusodo, Makassar - Hasanuddin Hasanuddin; Muh. Nur Ikhsan Liwang (Biology Department, Mathematics and natural science, Tadulako University, 2010)
This research is descriptive research that aims to provide an overview of nosocomial infections by age, gender, classroom treatment, duration of treatment, and manifestations of disease. The population is patients who are hospitalized in the Internal Medicine Ward Lontara 1 Bawah of the hospital Dr. Wahidin Sudirohusodo as many as 1,400 people. Population who meet the selection criteria sample of 987 people. Then do the sampling technique based on proportional stratified simple random sampling with a large sample of 245 people, from 2nd class treatment rooms as many as 74 people and from 3rd treatment rooms as many as 171 people. Data collected by examining patients' medical records. Data collected were analyzed using a calculator and then tabulate the results of the analysis are presented in tables, charts and explanations. Based on analysis of data found in patients with nosocomial infection as many as 46 people, or approximately 18.78% with the number of cases as many as 46 cases or approximately 18.78%. Patients with the highest nosocomial infection found in adult age group of 71.74%, male sex as much as 52.17%, of patients with long treatment by 41.30% 70-20 days, patients treated 3rd class treatment room as much as 71, 74% and wound infection infusion of 91.32%. Therefore, it is advisable to apply universal precautions procedures, cleanliness of food and beverages must be maintained and limit visitors at the hospital. Key words: Nosocomial, infection, and infusion.